(untitled) (Research Nepal Journal of Development Studies, 2021)
In 2015, the Vietnam’s Renewable Energy Development Strategy up to 2020 with an outlook to 2050 was approved. Renewable energy sources were developing to ensure energy security and addressing the growing power demand of the country. Increasing renewable energy sources such as biomass, solar, wind and small hydro is the way to shift Vietnam to a sustainable energy future. The general picture on Vietnamese renewable energy practice and experience are presented in this paper. Also it offers suggestion the technical and political keys to minimize the barriers in renewable energy sector. It is the general review of available sources on Green technology for sustainable development: Practice and experience of renewable energy in Vietnam. In conclusion the study gives brief status of energy barriers, biomass, renewable energy, small-hydro power, solar power, and wind power of Vietnam